Differentiated Learning Management as a Catalyst for Positive School Culture Development in Kindergarten Settings - Sayidah, Istiarah; Hidayat, Hidayat (Papanda Publisher, 2025)
Contemporary educational paradigms increasingly emphasize addressing student diversity through pedagogically responsive approaches. This study investigates how differentiated learning management serves as a catalyst for positive school culture development in kindergarten settings, addressing the gap between individual accommodation strategies and collective community building. A qualitative multiple case study was conducted at two kindergarten institutions in Sukabumi City, Indonesia: TK Negeri Pembina Baros and TK Aisyiyah 2. Six participants including two principals and four teachers were selected through purposive sampling. Data collection employed semi-structured interviews, classroom observations, and documentation analysis. Data analysis followed Creswell's framework using systematic coding procedures with NVivo software, incorporating methodological triangulation and member checking for validation. Four interconnected dimensions of differentiated learning management emerged: comprehensive planning that prioritizes student diversity recognition, robust organizational structures supporting implementation, diverse classroom strategies fostering inclusion, and systematic evaluation ensuring continuous improvement. Findings revealed that systematic adaptation of content, processes, and products creates inclusive environments where individual accommodation simultaneously contributes to positive culture development. Teachers demonstrated sophisticated professional competence in managing multiple differentiated activities while maintaining supportive learning atmospheres characterized by enhanced student engagement, respectful peer interactions, and collaborative behaviors. The results demonstrate a reciprocal relationship between differentiated learning and positive culture development, extending current theoretical frameworks. Findings align with culturally responsive classroom management principles and support the need for comprehensive institutional commitment rather than isolated teacher efforts. The study contributes empirical evidence for systematic approaches that honor student diversity while building strong learning communities, with implications for teacher preparation programs and educational policy development.